Creosote bush-derived NDGA attenuates molecular and pathological changes in a novel mouse model of non-alcoholic steatohepatitis (NASH). (1st December 2019) - Han, Lu; Bittner, Stefanie; Dong, Dachuan; Cortez, Yuan; Dulay, Hunter; Arshad, Sara; Shen, Wen-Jun; Kraemer, Fredric B.; Azhar, Salman
Abstract: Creosote bush ( Larrea tridentata )-derived nordihydroguaiaretic acid (NDGA) was shown to have profound effects on the core components of metabolic syndrome. This study investigated the in vivo potential of NDGA for prevention or attenuation of the pathophysiologic abnormalities of NASH. A novel dietary NASH model with feeding C57BL/6J mice with a high trans-fat, high cholesterol and high fructose (HTF) diet, was used. The HTF diet fed mice exhibited obesity, insulin resistance, hepatic steatosis, fibrosis, inflammation, ER stress, oxidative stress, and liver injury. NDGA attenuated these metabolic abnormalities as well as hepatic steatosis and fibrosis together with attenuated expression of genes encoding fibrosis, progenitor and macrophage markers with no effect on the levels of mRNAs for lipogenic enzymes. NDGA increased expression of fatty acid oxidation genes. In conclusion, NDGA exerts anti-NASH/anti-fibrotic actions and raises the therapeutic potential of NDGA for treatment of NASH patients with fibrosis and other associated complications. Highlights: Mice when fed a novel NASH diet develop obesity, insulin resistance, steatosis, fibrosis, inflammation, ER/oxidative stress and liver injury. NDGA ameliorates these metabolic abnormalities and improved hepatic steatosis and fibrosis and NASH pathology. NDGA attenuated expression of key genes involved in fibrosis, progenitor and macrophage markers with little or no effect on lipogenic genes. NDGA exerts anti-NASH/anti-fibrotic actions and has therapeutic potential for treatment of patients with NASH.